Bernal and the genesis of structural biology. - CAFFREY, MARTIN (My University, 2007)
I was invited to participate in this Symposium a month or so before the event. At that time however, I knew little about J D Bernal. I vaguely remembered a brief conversation on the topic over a decade ago with Professor Vittorio Luzzati as we ambled around the gardens at the Palace of Varsailles. Vittorio likely knew Bernal through his friend Rosalind Franklin who worked with Bernal at Birbeck College. But beyond that I knew nothing about the man or his science. And so it was most fortunate that Andrew Brown?s book J D Bernal: The Sage of Science [1] appeared in 2005 and I was able to call on it. Indeed, much of the material included in this chapter is based on that source and on Dorothy Hodgkin?s biographic memoir of J D Bernal [2], her postgraduate supervisor. Given that this chapter is to be published in a Physics journal I thought it appropriate to provide some background to the theme of my presentation, structural biology. Accordingly, I will begin with an introduction to proteins, one of structural biology?s central characters, and to which Bernal devoted much energy and attention. How the molecular structure of a protein determines its activity and function will then be described. Bernal?s major contribution in this area was to X-ray crystallography, the primary method by which a protein?s structure is determined. The method, and aspects of its development, will be described. I will also make reference to some of Bernal?s additional contributions in related fields. Finally, Vincent Casey, the symposium organizer, asked that I comment on how structural biology might impact on society. I will attempt to address that at the close of my presentation.
PUBLISHED
Keywords: Biophysics; J D Bernal